Head and neck cancer in South Asia: Macroeconomic consequences and the role of the head and neck surgeon. Issue 8 (30th March 2016) - Alkire, Blake C.; Bergmark, Regan W.; Chambers, Kyle; Lin, Derrick T.; Deschler, Daniel G.; Cheney, Mack L.; Meara, John G.
Abstract: Background: Head and neck cancer constitutes a substantial portion of the burden of disease in South Asia, and there is an undersupply of surgical capacity in this region. The purpose of this study was to estimate the economic welfare losses due to head and neck cancer in India, Pakistan, and Bangladesh in 2010. Methods: We used publicly available estimates of head and neck cancer morbidity and mortality along with a concept termed the value of a statistical life to estimate economic welfare losses in the aforementioned countries in 2010. Results . Economic losses because of head and neck cancer in India, Pakistan, and Bangladesh totaled 16.9 billion (2010 US dollars [USD]), equivalent to 0.26% of the region's economic output. Bangladesh, the poorest country, experienced the greatest proportional losses. Conclusion: The economic consequences of head and neck cancer in South Asia are significant, and building surgical capacity is essential to begin to address this burden. © 2016 Wiley Periodicals, Inc. Head Neck 38:1242–1247, 2016